Pemberdayaan UMKM Percetakan SMArt Melalui Pelatihan Digital Marketing - Meilinda, Eva; Saputra, Dedi; Murni, Sri (PELITA NUSA TENGGARA, 2025)
This study aims to enhance the capacity of the Smart printing SMEs through digital marketing training to expand market reach and improve competitiveness. With the rapid advancement of technology, SMEs in Indonesia, including the printing sector, face challenges in adapting to digitalization, which can increase marketing and sales efficiency. The training focuses on introducing digital marketing tools and strategies, such as social media utilization, search engine optimization (SEO), and digital advertising on platforms like Facebook, Instagram, and Google Ads. The training method combines hands-on practice and case studies, ensuring participants can directly apply the knowledge learned. The expected outcomes of this activity include improved digital marketing skills among the printing SME owners, which will lead to increased sales, market expansion, and operational efficiency. Therefore, this training not only imparts knowledge but also empowers SMEs to become more independent and competitive in an increasingly digital market. This activity is expected to serve as a model for the development of other SMEs in sectors that require similar digital transformation.